Bone biology: insights from osteogenesis imperfecta and related rare fragility syndromes. (5th July 2019) - Besio, Roberta; Chow, Chi‐Wing; Tonelli, Francesca; Marini, Joan C.; Forlino, Antonella
Abstract : Recent breakthroughs in the identification of mutant proteins affecting bone tissue homeostasis in rare skeletal diseases have revealed novel pathways involved in skeletal development and maintenance. The characterization of new forms of the rare brittle bone disease osteogenesis imperfecta and other related bone fragility disorders was a key player in this advance and will likely allow the identification of new targets to develop novel therapies for currently incurable diseases. Abstract : The limited accessibility of bone and its mineralized nature have restricted deep investigation of its biology. Recent breakthroughs in identification of mutant proteins affecting bone tissue homeostasis in rare skeletal diseases have revealed novel pathways involved in skeletal development and maintenance. The characterization of new dominant, recessive and X‐linked forms of the rare brittle bone disease osteogenesis imperfecta (OI) and other OI‐related bone fragility disorders was a key player in this advance. The development of in vitro models for these diseases along with the generation and characterization of murine and zebrafish models contributed to dissecting previously unknown pathways. Here, we describe the most recent advances in the understanding of processes involved in abnormal bone mineralization, collagen processing and osteoblast function, as illustrated by the characterization of new causative genes for OI and OI‐related fragility syndromes. The coordinated role of the integral membrane protein BRIL and of the secreted protein PEDF in modulating bone mineralization as well as the function and cross‐talk of the collagen‐specific chaperones HSP47 and FKBP65 in collagen processing and secretion are discussed. We address the significance of WNT ligand, the importance of maintaining endoplasmic reticulum membrane potential and of regulating intramembrane proteolysis in osteoblast homeostasis. Moreover, we also examine the relevance of the cytoskeletal protein plastin‐3 and of the nucleotidyltransferase FAM46A. Thanks to these advances, new targets for the development of novel therapies for currently incurable rare bone diseases have been and, likely, will be identified, supporting the important role of basic science for translational approaches.